Does Stone Culture Predict Systemic Inflammatory Response after Percutaneous Nephrolithotomy? - Luitel, BR; Chalise, PR; Gyawali, PR; Sharma, UK; Shrestha, GK; Joshi, BR (Journal of Institute of Medicine Nepal, 2014)
Introduction: Systemic inflammatory response syndrome (SIRS) is a common and important complication after percutaneous nephrolithotomy (PNL). This study was carried out with the objective of finding out the association between stone culture and PostPNL- SIRS.Methods: A prospective study was done in the urology unit, Tribhuvan University Teaching Hospital from July 2009 to June 2011. Preoperative midstream urine, intraoperative pelvic urine and stone fragments were sent for culture in all patients undergoing PNL. The primary outcome was SIRS on second postoperative day. Data analysis was done using Statistical Package for Social Sciences (SPSS) 17.0 version.Results: Out of 47 patients 22 (46.8%) patients developed SIRS on second postoperative day. Stone and pelvic urine culture positivity rate was 8(17%) and 6(12.8%) respectively with P. aeruginosa E. coli and Proteus spp being the common organisms isolated, most of which were sensitive to amikacin. Positive stone culture was the significant risk factor for SIRS (P=0.018).Conclusion: Positive stone culture is an important risk factor for SIRS after PNL. Routine stone culture is beneficial in patients undergoing PNL for the subsequent postoperative management.